Pengaruh Pemberian Biourin Sapi terhadap Pertumbuhan dan Produksi Tanaman Kangkung Darat (Ipomoea reptans Poir) pada Tanah Ultisol - Maya Pahlawati; Muhammad Mahbub; Muhammad Syarbini (Acta Solum, 2022)
Ultisols have the potential to be developed as productive agricultural land, but need several efforts by means of organic matter and fertilizer applications. Biourine is a fermented liquid waste from cow urine. One of the commodities developed in Ultisol is spinach (Ipomoea reptans Poir). The study aims to determine the effect of treatments of six biourin concentrations on available nitrogen, soil pH, and growth plants of spinach on Ultisol soil. The single factor of completely randomized design (CRD) used as an experimental design consists of six treatments with four replications (24 experimental units). The results showed that biourine had no effect on increasing soil ammonium-N and had no effect on soil nitrate-N and soil pH. Biourin affects the increase in wet weight and dry weight of spinach plants. There is a relationship between soil NO3- and NH4+ levels with wet weight. Biourin concentration level of 2% is the best concentration to increase ammonium-N, wet weight and dry weight.